Pripovedni svet Brede Smolnikar - Juvan, Marko (Slavistična revija, 2016)
Breda Smolnikar's storytelling derives from life narratives, oral history, and collective and personal memories linked to the suburban socio-economic structure of the sub-Alpine Kamnik-Domžale Plain. However, her writing transcends this material by transforming it into a singular poetic fiction through which Smolnikar addresses a broader and socio-spatially unspecified audience. At the level of literary mediation, the emancipatory features of "feminine writing" in the structure and themes of Smolnikar's narratives coincide with the artist's insistence on the independence of self-publishing.
Keywords: collective memory; fiction; fikcija; kolektivni spomin; oral history; samozaložništvo; self-publishing; Slovene literature; Slovene women writing; slovenska književnost; slovenska proza; slovenske pisateljice; Smolnikar, Breda, 1941-; ustna zgodovina; žensko pisanje